2016
DOI: 10.1097/qai.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Infected Ugandan Women on Antiretroviral Therapy Maintain HIV-1 RNA Suppression Across Periconception, Pregnancy, and Postpartum Periods

Abstract: Background HIV-infected women risk sexual and perinatal HIV transmission during conception, pregnancy, childbirth, and breastfeeding. We compared HIV-1 RNA suppression and medication adherence across periconception, pregnancy, and postpartum periods, among women on ART in Uganda. Methods We analyzed data from women in a prospective cohort study, aged 18-49 years, enrolled at ART initiation and with ≥ 1 pregnancy between 2005-2011. Participants were seen quarterly. The primary exposure of interest was pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…The same study found that pregnancy incidence was 10.2 per 100 person-years (n = 1785) in women on PrEP indicating that PrEP may be acceptable and feasible as a SCS in HIV-uninfected women with HIV-infected partners. Matthews et al found that Ugandan HIV-infected women trying to conceive had highest levels of ART adherence during peri-conception periods (adjusted odds ratio [aOR] 2.15, 95% CI 1.33, 3.49) when compared to non-pregnant women during a six-year study [58]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study found that pregnancy incidence was 10.2 per 100 person-years (n = 1785) in women on PrEP indicating that PrEP may be acceptable and feasible as a SCS in HIV-uninfected women with HIV-infected partners. Matthews et al found that Ugandan HIV-infected women trying to conceive had highest levels of ART adherence during peri-conception periods (adjusted odds ratio [aOR] 2.15, 95% CI 1.33, 3.49) when compared to non-pregnant women during a six-year study [58]. …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were qualitative assessments of healthcare providers and people living with HIV or serodiscordant couples. Several studies found that providers rarely initiated discussion of fertility intentions and reproductive goals with HIV-affected clients during visits [24, 39, 41, 42, 46, 50, 58, 65]. When fertility intentions were assessed, usually only the woman’s reproductive goals were discussed and not the man’s or couples [58, 61].…”
Section: Resultsmentioning
confidence: 99%
“…21 In contrast, a cohort in western Uganda reported that women who initiated ART for clinical indications (median CD4 count 165 cells/mm 3 ) were able to maintain high levels (>89%) of viral suppression to ≤400 copies/ml subsequently during pregnancy and up to 6 months postpartum. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Viral suppression rates decrease gradually from nonpregnant state to postpartum period [18]. Although the PMTCT programme coverage in South Africa has been successful in nearly eliminating MTCT, postpartum virologic suppression is the key for further reductions of postpartum transmission rates [20].…”
Section: Discussionmentioning
confidence: 99%